The Impact of Human Resource Management Function on Organization Commitment from Islamic Perspective - Elmakawi, Zienab; Abdelkarim, Yousif (The Arab Journal of Administration, 2023)
This study brings into focus the extent of Islamic human resource management in Islamic bank in Sudan and its impact on organizational commitment. The purpose of this study was to identify Islamic Human resource practices and organizational commitments that affect employee retention in Sudan with emphasis on banking sector. The Islamic HRM practices proposed in this study, such as recruitment and selection, training and development and performance appraisal. To accomplish this task, quantitative research approaches engaged. The surveys consisted of demographic information, Islamic human resource. The research study indicated significant correlation between Islamic human resource practicing and organizational commitment. As with many organizations worldwide, staff retention problems affect organizational productivity and performance.